The Correlation between Students’ Grammar Mastery and Students’ Reading Comprehension - Aldila Fani Prasetia; Eliza Eliza; Veni Roza; Reflinda Reflinda (Journal of English Language and Education, 2022)
New vocabulary or unknown word becomes problem for students. When students read a text, they got difficult because the unknown word.  And students had difficulty in grammar mastery too. To get the meaning of the text, it needs grammar. In grammar has a adverbial of time which is it can use as clue when reading a text. Additionally, this research is aimed to know whether there is a significant correlation between the students’ grammar mastery and students’ reading comprehension at Ninthegrade of MTsS PP MIS Cubadak.The quantitative research method and the technique was correlation research. The population was 117 students and sample of this research was 39 students from 92 class which use purposive sampling technique. The data was collected by grammar mastery and reading comprehension test. For reading comprehension test which was adapted from national exam prediction for junior high school printed by graha pustaka.The finding of this research shows that there is significant correlation between theStudents’ grammar mastery and students’ reading comprehension. It is proved by the r-measured 0.856 which is higher than r-table 0.316 (0.856 0.316). There was positive correlation and has high correlation between 0.81 – 0.99 which mean it has very high correlation. This means that frequent grammar mastery can improve reading comprehension.Based on the finding above, the question of the researchs’ problem were answered. There was a significant correlation between students’ grammar mastery and students’ reading comprehension since r-measured bigger than r-table. There was positive correlation between students’ grammar mastery and students’ reading comprehension. It can be seen from the table 4.7 which there was no minus mark in the table. Correlation between students’ grammar mastery and students’ reading comprehension has very strong correlation. The more students learn about grammar, it can increase their knowledge about reading comprehension.